Visual Materials in Classroom Teaching Learning: A Case Study on Nonformal Primary School: A Case Study on Nonformal Primary School (Teacher’s World: Journal of Education and Research, 2024)
The evolution of technology and the paradigm shift triggered by the COVID-19 pandemic have reshaped educational practices, transitioning from conventional to digital mechanisms. The integration of digital learning resources has introduced a new dimension to the classroom environment. This paper aims to investigate the practicality of utilizing existing visual learning materials in non-formal educational settings. The case study focuses on non-formal primary schools operated by the JAAGO Foundation in Dhaka, serving as a representative sample. Data for this study were gathered through semi-structured interviews, focus group discussions, and observation notes from teachers, learners, and experts in the sampled non-formal primary schools. Thematic analysis was employed to analyze and present the collected data. The findings of the study underscore significant positive effects of employing visual learning materials in non-formal primary classrooms. These effects manifest in the areas of motivation enhancement, assessment of prior knowledge, and promotion of active participation, particularly among disadvantaged learners. The study also highlights the effectiveness of visual materials in facilitating clear comprehension, fostering creativity and imagination, enhancing critical thinking skills, and promoting digital literacy as essential 21st-century skills. Moreover, the research reveals that visual learning materials play a crucial role in achieving desired learning outcomes, aligning with both learners' psychology and pedagogical perspectives. However, the study identifies key challenges hindering the effective use of visual materials in non-formal classrooms, including infrastructural inconveniences such as poor projection systems, noisy sound systems, and inadequate seating arrangements for students. In light of these findings, the study recommends the implementation of professional training sessions for educators and emphasizes the need for school authorities to take responsibility in addressing identified challenges. By doing so, the study advocates for the creation of an environment conducive to effective classroom practices utilizing visual materials in non-formal educational settings.Teacher’s World: Journal of Education and Research, 49 (2),37-51